The inmersive virtual reality as tool for learning in architecture, civil engineering anda construction engineering - Sanchez Botero, Tatiana (2017)
This paper reports the results of the first experimental evidence of the application of virtual reality in Construction Engineering, which aims to make evident the advantages of the use of technological as teaching tools in Architecture, Civil Engineering and Construction Engineering. The test was conducted with students of Graphic Expression Techniques course, in the Civil Engineering program of EAFIT University, Medellín, in the topic of isometric interpretation and generation of its views. The results indicate the high acceptance of the tool and show the benefits of virtual reality for the graphical interpretation of some concepts in Architecture and Engineering.